2020
DOI: 10.1097/ijg.0000000000001728
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Prices and Eye-Care Providers Prescribing Patterns of Glaucoma Medications in the United States Between 2013 and 2019

Abstract: Precis: Brand glaucoma medication prices vastly increased in the United States over the past 7 years, despite a reduction in eye-care providers’ tendency to prescribe brand medications over generics. Purpose: Determine the changes in prices of brand and generic glaucoma medications and to identify changes in eye-care providers prescribing patterns since 2013. Materials and Methods: The National Average Drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…30 Medical therapy for glaucoma is an economic burden to many patients in that area, as many of them are not covered by any insurance plan/government reimbursement for their treatment. 31 The expenditure on antiglaucoma medications may exceed the monthly gross income. The low socioeconomic status of the population in that area, is reflected by the relatively small average number of hypotensive medications used preoperatively in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Medical therapy for glaucoma is an economic burden to many patients in that area, as many of them are not covered by any insurance plan/government reimbursement for their treatment. 31 The expenditure on antiglaucoma medications may exceed the monthly gross income. The low socioeconomic status of the population in that area, is reflected by the relatively small average number of hypotensive medications used preoperatively in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Choice of primary therapeutic modality needs to be made on an individual patient basis 30. Medical therapy for glaucoma is an economic burden to many patients in that area, as many of them are not covered by any insurance plan/government reimbursement for their treatment 31. The expenditure on antiglaucoma medications may exceed the monthly gross income.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 With advancements in glaucoma management including the introduction of optical coherence tomography (OCT) imaging and minimally invasive procedures and the higher costs of medication, the cost of treatment has increased since 2013. 4 Although a significant portion of health care resources are spent on glaucoma management, clinical outcomes can vary widely. Despite the resources and costs spent on glaucoma management, as recently as 2022, the US Preventative Services Task Force has concluded that there is insufficient evidence to support screening for glaucoma in asymptomatic patients aged 40 or older.…”
mentioning
confidence: 99%
“…For example, in 2006 total direct costs per year per patient ranged from $623 in glaucoma suspects or patients with earliest-stage disease to $2511 in end-stage disease 3 . With advancements in glaucoma management including the introduction of optical coherence tomography (OCT) imaging and minimally invasive procedures and the higher costs of medication, the cost of treatment has increased since 2013 4 . Although a significant portion of health care resources are spent on glaucoma management, clinical outcomes can vary widely.…”
mentioning
confidence: 99%